Chromosomal aberrations, sister chromatid exchanges, and urinary thioethers in nurses handling antineoplastic drugs - Sarto, F; Trevisan, A; Tomanin, R; Canova, A; Fiorentino, M (American journal of industrial medicine, 1990)
In this study we examined the structural chromosomal aberrations (CA) and sister chromatid exchanges (SCE) of 12 nurses handling moderate quantities of antineoplastic drugs. Urinary thioethers were also measured to assess the potential exposure to alkylating drugs. Two control groups with similar mean age and smoking habits and working in the same hospital were also studied: 1) control clerks and 2) control nurses. Our study did not show any clear increase of chromosomal damage in exposed nurses as compared to controls. However, CA in control nurses were significantly increased (p = 0.05) with respect to control clerks. The results of baseline urinary excretion of thioethers were statistically higher (p less than 0.02) in exposed subjects than in control clerks.